Depyrogenation Mechanism of Baicalin Solution with Activated Carbon - Zhi, X.L.; Li, C.Y.; Li, H.Y.; Peng, G.P. (Asian Journal of Chemistry, 2013)
In clinical practice, traditional Chinese medicine injections with the function of clearing away heat and toxic materials tend to cause pyrogen reaction. The pyrogen removal experiments showed that the activated carbon had the defection of applicability, especially in injections containing baicalin. To simulate a sudden pyrogen contamination in injections, the bacterial endotoxin indicator was added into aqueous solution of baicalin. As the activated carbon dosage increasing, a plateau of removal efficiency appeared, in which the removal efficiency of bacterial endotoxin was not significantly improved. However, the loss of baicalin was markedly increased. Besides, the comparison between two kinds of manufacturing techniques of traditional Chinese medicine injections containing baicalin showed that competitive adsorption existed between bacterial endotoxin and baicalin. Therefore, during the injection production, interactions among manufacturing techniques, compositions and harmful substances should be definitely clear, which makes a far-reaching significance on the quality promotion of injections.